Effect of excess Fe2O3 content on microstructure and tensile properties of 304 stainless steel with dual nanocrystalline and microcrystalline austenite prepared by aluminothermic reaction casting - Лиу Haibin; Wеи Ying; Ла Peiqing; Хан Yijun; Ли Zhengning; Схи Yu (Materials. Technologies. Design, 2019)
Microstructures of the 304 stainless steels, with nanocrystalline and microcrystalline austenite prepared by an aluminothermic reaction casting with different contents of Fe2O3 in reactants, have been investigated by XRD, SEM and EDS, and TEM. The results show that with the increase of the excessive content of Fe2O3 in the reactants, the content of Al remained in the steels decreased firstly and then increased, while the content of other alloying elements such as Cr, Ni decreased. When Fe2O3 was 5 wt.% in the reactants, the amount of Al and the ferrite content reached the minimum. The cast 304 austenitic stainless steel prepared with the excess Fe2O3 of 5wt% was mainly composed of microcrystalline, nanocrystalline austenite and a little microcrystalline ferrite. The volume fraction of the nanocrystalline austenite in the steel was about 67% when Fe2O3 was 5 wt.% in the reactants and the tensile strength of the cast steel was 674 MPa, the yield strength was 458 MPa, and the elongation rate was 10.4 %.